Free A*-algebras - Srinivasa Rao, T; Koteswara Rao, P (Journal of Experimental Sciences, 2012)
In this paper we studied the free A*-algebras, the sub A*-algebra generated by a subset and its characterization, an A*-algebra freely generated by a subset and introduced the concept of A*-field of sets. Also we established some theorems on making A*-field of sets into A*-algebras.